Эволюция, филогенез и система тлей семейства ляхнид (Aphidinea, Lachnidae). Сообщение II - Мамонтова, В.А. (Вестник зоологии, 1980)
The paper is concerned with evolution ways of Lachnidae, their place in the system of plant lices, phylogeny and some principles of phylogenetic schemes construction, relationships in the system of the family under study as reflected in the general classification scheme.